Liquid crystal-based polymer solid electrolyte composition, liquid crystal-based polymer solid electrolyte, preparation method of liquid crystal-based polymer solid electrolyte and lithium metal battery

By using liquid crystal-based polymer solid electrolyte compositions in lithium metal batteries, a continuous and directional arrangement of polymer network is formed, which solves the safety hazards and stability problems of traditional lithium-ion batteries, and achieves the improvement of the stable operation and cycle life of lithium-ion batteries at room temperature.

CN119920967APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311433397.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have problems such as electrolyte leakage caused by the puncture of lithium dendrites in the internal battery and damage to the outer packaging, which poses safety risks of fire, combustion and explosion, and are insufficient electrochemical stability and thermal stability.

Method used

The liquid crystal-based polymer solid electrolyte composition is adopted, including polymerizable nematic liquid crystal monomers, acrylate monomers, ionic liquids, lithium salts, crosslinking agents and initiators, and a continuous and directional arrangement of polymer networks are formed by copolymerization, providing physical support and forming an ionic liquid channel, and promoting the rapid transportation of lithium ions.

Benefits of technology

It realizes the stable operation of lithium metal batteries at room temperature, improves the cycle life and safety performance of the batteries, and reduces the risk of fire, combustion and explosion caused by electrolyte leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920967A_ABST
    Figure CN119920967A_ABST
Patent Text Reader

Abstract

The invention relates to a liquid-crystal-based polymer solid electrolyte composition, a liquid-crystal-based polymer solid electrolyte, a preparation method of the liquid-crystal-based polymer solid electrolyte and a lithium metal battery. The liquid-crystal-based polymer solid electrolyte composition comprises a polymerizable nematic liquid crystal monomer, an acrylate monomer, an ionic liquid, a lithium salt, a cross-linking agent and an initiator, the polymerizable nematic liquid crystal monomer comprises a bifunctional liquid crystal monomer. The liquid-crystal-based polymer solid electrolyte composition provided by the invention contains the polymerizable nematic liquid crystal monomer and the acrylate monomer, can form a continuously and directionally arranged polymer network, and provides a path for rapid transportation of lithium ions, so that a lithium metal battery can operate stably.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of solid electrolytes, and in particular, to a liquid crystal based polymer solid electrolyte composition, a liquid crystal based polymer solid electrolyte, a preparation method thereof, and a lithium metal battery. Background Art

[0002] Lithium batteries have attracted wide attention in the fields of 3C electronic products, electric vehicles, large-scale energy storage, and artificial intelligence due to their advantages such as high energy density, high operating voltage, long cycle life, and low production cost. However, for traditional lithium-ion batteries, there are safety issues such as battery fire, combustion, and explosion caused by lithium dendrites piercing the diaphragm and electrolyte leakage caused by damage to the outer packaging, poor quality safety, and insufficient electrochemical and thermal stability. A large number of researchers have turned to safer solid-state batteries.

[0003] The current solid electrolyte systems mainly include oxides, sulfides, polymers and composite solid electrolytes. Among them, polymer solid electrolytes have attracted extensive attention due to their excellent flexibility and interface properties, as well as the ability to be processed over a large area. However, the inherent low ionic conductivity and interface impedance of solid electrolytes at room temperature make it difficult for them to replace liquid electrolytes for large-scale commercial applications. Summary of the invention

[0004] The purpose of the present disclosure is to provide a liquid crystal-based polymer solid electrolyte composition, a liquid crystal-based polymer solid electrolyte, a preparation method thereof, and a lithium metal battery. The liquid crystal-based polymer solid electrolyte composition contains a polymerizable nematic liquid crystal monomer and an acrylate monomer, which can form a continuous and directional polymer network, provide a path for the rapid transport of lithium ions, and enable the lithium metal battery to operate stably at room temperature.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a liquid crystal-based polymer solid electrolyte composition, which includes a polymerizable nematic liquid crystal monomer, an acrylate monomer, an ionic liquid, a lithium salt, a cross-linking agent and an initiator; the polymerizable nematic liquid crystal monomer includes a bifunctional liquid crystal monomer.

[0006] Optionally, the polymerizable nematic liquid crystal monomer has a structure as shown in the following formula (1):

[0007]

[0008] In formula (1), n1~n2 represent the number of -CH2-CH2-, n1~n2 are the same or different, and are independently selected from any integer between 1 and 9, preferably selected from any integer between 3 and 6; R1~R5 are the same or different, and are independently selected from hydrogen, halogen group, cyano group, alkyl group with 1 to 5 carbon atoms, haloalkyl group with 1 to 2 carbon atoms, alkoxy group with 1 to 2 carbon atoms; preferably, R1~R5 are the same or different, and are independently selected from one or more of hydrogen, halogen group, cyano group, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; x represents the number of R3, x is 0 or 1; y represents the number of R4, y is 0 or 1; z represents the number of R5, z is 0 or 1.

[0009] Optionally, the polymerizable nematic liquid crystal monomer is selected from one or more of 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-methacryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-ethylacryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-ethylbenzene, 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene and 1,4-bis[4-(6-acryloxyhexyloxy)-3-methylbenzoyloxy]-2-methylbenzene.

[0010] Optionally, the acrylate monomer has a -CH2-CH2-O- structure, and the acrylate monomer includes one or more of a monofunctional acrylate monomer, a difunctional acrylate monomer, and a multifunctional acrylate monomer. Preferably, the acrylate monomer includes at least one difunctional acrylate monomer; the molecular weight of the difunctional acrylate monomer is 180 to 10,000; more preferably, the difunctional acrylate monomer has a structure as shown in the following formula (2): In formula (2), m represents the number of -CH2-CH2-O-, and m is selected from any integer between 1 and 10, preferably selected from any integer between 1 and 5; further preferably, the acrylate monomer is selected from one or more of ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate and pentaethylene glycol dimethacrylate.

[0011] Optionally, the crosslinking agent is selected from a thiol crosslinking agent, and the thiol crosslinking agent is selected from one or more of tetrakis(3-mercaptopropionic acid) pentaerythritol ester, (3-mercaptopropionic acid) ethylene glycol ester, trimethylolpropane tris(3-mercaptopropionic acid), hexa(3-mercaptopropionic acid) dipentaerythritol ester and 1,4-butanediol di(3-mercaptopropionic acid); the ionic liquid is selected from imidazole ionic liquids and / or pyrrole ionic liquids, the cation of the imidazole ionic liquid is selected from substituted or unsubstituted imidazole cations, and the anion of the imidazole ionic liquid is selected from one or more of halogen anions, halogenated phosphate anions, halogenated alkane anions, halogenated sulfonyl imide anions and halogenated sulfonic acid anions; preferably, the imidazole ionic liquid is selected from 1-ethyl-3-methylimidazole bis(trifluoromethyl)imidazolium The invention relates to a novel ionic liquid comprising: a 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, a 1-ethyl-3-methylimidazolium chloride, a 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, a 1-ethyl-3-methylimidazolium hexafluorophosphate and a 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt; the pyrrole ionic liquid is selected from 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide and / or 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide; the lithium salt is selected from one or more of bis(trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium salt, lithium hexafluorophosphate and lithium chloride; the initiator is selected from a photoinitiator, and the photoinitiator is selected from one or more of 1-hydroxycyclohexylphenyl ketone, α-hydroxyisobutyrophenone and 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

[0012] Optionally, relative to 100.8 parts by weight of the liquid crystal-based polymer solid electrolyte composition, the content of the polymerizable nematic liquid crystal monomer is 15 to 25% by weight, preferably 18 to 22% by weight; the content of the acrylate monomer is 30 to 50% by weight, preferably 35 to 45% by weight; the content of the ionic liquid is 10 to 20% by weight, preferably 13 to 17% by weight; the content of the lithium salt is 10 to 20% by weight, preferably 14 to 16% by weight; the content of the cross-linking agent is 5 to 15% by weight, preferably 8 to 12% by weight; the content of the initiator is 0.5 to 1.0% by weight, preferably 0.7 to 0.9% by weight.

[0013] Optionally, the weight ratio of the polymerizable nematic liquid crystal monomer to the cross-linking agent is (0.8-3):1, preferably (1.2-2.5):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the acrylic monomer is (0.3-0.8):1, preferably (0.4-0.6):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the ionic liquid is (0.5-2):1, preferably (1.2-1.5):1.

[0014] The second aspect of the present disclosure provides a method for preparing a liquid crystal based polymer solid electrolyte using the liquid crystal based polymer solid electrolyte composition according to the first aspect of the present disclosure, the method comprising:

[0015] (1) mixing the liquid crystal based polymer solid electrolyte composition with an organic solvent and stirring to obtain a polymer precursor solution;

[0016] (2) In-situ polymerization of the polymer precursor solution under ultraviolet light to obtain a liquid crystal based polymer solid electrolyte.

[0017] Optionally, in step (1), the weight ratio of the liquid crystal-based polymer solid electrolyte composition to the organic solvent is (1-2.5):1, preferably (1.3-1.8):1; the organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, anhydrous acetonitrile and acetone; in step (2), the conditions for the in-situ polymerization include: the wavelength of the ultraviolet light is 340-380nm, the light intensity is 20-40mW / cm 2 ; The temperature of in-situ polymerization is 25-35°C and the time is 20-35min.

[0018] A third aspect of the present disclosure provides a liquid crystal-based polymer solid electrolyte prepared by the method described in the second aspect of the present disclosure.

[0019] Optionally, the liquid crystal based polymer solid electrolyte is in the form of a film, and the thickness of the film-like liquid crystal based polymer solid electrolyte is 50 to 300 μm, preferably 120 to 200 μm.

[0020] A fourth aspect of the present disclosure provides a lithium metal battery, the lithium metal battery comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the electrolyte is the liquid crystal-based polymer solid electrolyte described in the third aspect of the present disclosure.

[0021] Through the above technical scheme, the present disclosure provides a liquid crystal-based polymer solid electrolyte composition, a liquid crystal-based polymer solid electrolyte and a preparation method thereof, and a lithium metal battery. The solid electrolyte composition contains a polymerizable nematic liquid crystal monomer and an acrylate monomer. The liquid crystal monomer and the acrylate monomer are copolymerized to form a continuous directional polymer network. The polymer network can not only provide sufficient physical support for the solid electrolyte film, but also the phase separation structure formed by the internal directional porous network structure can constitute a continuous ion liquid channel, providing a path for the rapid transport of lithium ions, so that the lithium metal battery can operate stably at room temperature.

[0022] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0024] Figure 1 are scanning electron microscope images of the surface (left) and cross section (right) of the liquid crystal-based polymer solid electrolyte prepared in Example 1 of the present disclosure;

[0025] Figure 2 A curve diagram showing the change of ionic conductivity of the liquid crystal based polymer solid electrolyte prepared in Example 1 of the present disclosure with temperature;

[0026] Figure 3 This is a battery cycle performance diagram of a lithium metal battery made of a liquid crystal-based polymer solid electrolyte according to Example 1 of the present disclosure at a current density of 1C, wherein the positive electrode is a lithium iron phosphate material (LFP). DETAILED DESCRIPTION

[0027] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0028] The first aspect of the present disclosure provides a liquid crystal-based polymer solid electrolyte composition, which includes a polymerizable nematic liquid crystal monomer, an acrylate monomer, an ionic liquid, a lithium salt, a cross-linking agent and an initiator; the polymerizable nematic liquid crystal monomer includes a bifunctional liquid crystal monomer.

[0029] The liquid crystal-based polymer solid electrolyte composition provided by the present invention contains a polymerizable nematic liquid crystal monomer and an acrylate monomer, and the liquid crystal monomer and the acrylate monomer are copolymerized to form a continuous directional polymer network, which can not only provide sufficient physical support for the solid electrolyte film, but also the phase separation structure formed by the internal directional porous network structure can constitute a continuous ion liquid channel, providing a path for the rapid transport of lithium ions, so that the lithium metal battery can operate stably at room temperature.

[0030] In one embodiment of the present disclosure, the polymerizable nematic liquid crystal monomer has a structure as shown in the following formula (1):

[0031]

[0032] In formula (1), n1~n2 represent the number of -CH2-CH2-, n1~n2 are the same or different, and are independently selected from any integer between 1 and 9, preferably selected from any integer between 3 and 6; R1~R5 are the same or different, and are independently selected from hydrogen, halogen group, cyano group, alkyl group with 1 to 5 carbon atoms, haloalkyl group with 1 to 2 carbon atoms, alkoxy group with 1 to 2 carbon atoms; preferably, R1~R5 are the same or different, and are independently selected from one or more of hydrogen, halogen group, cyano group, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; x represents the number of R3, x is 0 or 1; y represents the number of R4, y is 0 or 1; z represents the number of R5, z is 0 or 1. In the above embodiment, the polymerizable nematic liquid crystal monomer has an orientation property under an electric field, which can regularize the orientation structure inside the polymer network and realize a low-bending and long-range ordered phase separation structure, thereby achieving a more uniform lithium ion transmission efficiency and effectively improving the cycle life and safety performance of lithium metal batteries.

[0033] In a specific embodiment, the polymerizable nematic liquid crystal monomer is selected from 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (structural formula: Where n1 to n2 are 3, R1 to R4 are hydrogen, R5 is methyl, x, y, z are 1), 1,4-bis[4-(6-methacryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (structural formula is Where n1 to n2 are 3, R1 to R2 are methyl, R3 to R4 are hydrogen, R5 is methyl, x, y, z are 1), 1,4-bis[4-(6-ethylacryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (structural formula is Where n1 to n2 are 3, R1 to R2 are ethyl, R3 to R4 are hydrogen, R5 is methyl, x, y, z are 1), 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-ethylbenzene (structural formula is Where n1 to n2 are 3, R1 to R4 are hydrogen, R5 is ethyl, x, y, z are 1), 1,4-bis[4-(6-acryloyloxyhexyloxy)-2-methylbenzoyloxy]-2-methylbenzene (structural formula is Where n1-n2 are 3, R1-R2 are hydrogen, R3-R5 are methyl, x, y, z are 1) and 1,4-bis[4-(6-acryloyloxyhexyloxy)-3-methylbenzoyloxy]-2-methylbenzene (structural formula is Wherein n1~n2 are 3 respectively, R1~R2 are hydrogen respectively, R3~R5 are methyl respectively, and x, y, z are one or more of 1).

[0034] In one embodiment of the present disclosure, the acrylate monomer has a -CH2-CH2-O- structure, and the acrylate monomer includes one or more of a monofunctional acrylate monomer, a difunctional acrylate monomer, and a multifunctional acrylate monomer. Preferably, the acrylate monomer includes at least one difunctional acrylate monomer; the molecular weight of the difunctional acrylate monomer is 180 to 10,000.

[0035] In a preferred embodiment, the difunctional acrylate monomer is a polyether bond polyacrylate monomer. For example, the difunctional acrylate monomer has a structure as shown in the following formula (2): In formula (2), m represents the number of -CH2-CH2-O-, and m is selected from any integer between 1 and 10, preferably any integer between 1 and 5; further preferably, the acrylate monomer is selected from one or more of ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and pentaethylene glycol dimethacrylate. In the above embodiment, the preferred difunctional acrylate monomer is selected to form a complete three-dimensional polymer network structure.

[0036] In one embodiment of the present disclosure, the crosslinking agent is selected from a thiol crosslinking agent, and the thiol crosslinking agent is selected from one or more of tetrakis(3-mercaptopropionic acid)pentaerythritol ester, (3-mercaptopropionic acid)ethylene glycol ester, trimethylolpropane tris(3-mercaptopropionate), hexa(3-mercaptopropionic acid)dipentaerythritol ester and 1,4-butanediol di(3-mercaptopropionate). In the above embodiment, the selection of a preferred crosslinking agent is conducive to better connection of polymer monomers.

[0037] In the present disclosure, the ionic liquid is selected from imidazolium ionic liquids and / or pyrrole ionic liquids. In one embodiment, the cation of the imidazolium ionic liquid is selected from substituted or unsubstituted imidazolium cations, and the anion of the imidazolium ionic liquid is selected from one or more of halogen anions, halogenated phosphate anions, halogenated alkane anions, halogenated sulfonyl imide anions and halogenated sulfonic acid anions; preferably, the imidazolium ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium hexafluorophosphate and 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide. In another embodiment, the pyrrole ionic liquid is selected from 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide and / or 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide. In the above embodiment, the use of high boiling point imidazole ionic liquid and / or pyrrole ionic liquid not only greatly increases the thermal stability of the solid electrolyte, but also improves the stable operation capability of the battery at room temperature. At the same time, the ionic liquid also has a certain mechanical strength, which can inhibit the growth of lithium dendrites to a certain extent.

[0038] In one embodiment, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium chloride; the initiator is selected from a photoinitiator, and the photoinitiator is selected from one or more of 1-hydroxycyclohexylphenyl ketone, α-hydroxyisobutyrophenone and 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

[0039] In one embodiment of the present disclosure, relative to 100.8 parts by weight of the liquid crystal-based polymer solid electrolyte composition, the content of the polymerizable nematic liquid crystal monomer is 15-25% by weight, preferably 18-22% by weight; the content of the acrylate monomer is 30-50% by weight, preferably 35-45% by weight; the content of the ionic liquid is 10-20% by weight, preferably 13-17% by weight; the content of the lithium salt is 10-20% by weight, preferably 14-16% by weight; the content of the cross-linking agent is 5-15% by weight, preferably 8-12% by weight; the content of the initiator is 0.5-1.0% by weight, preferably 0.7-0.9% by weight.

[0040] In one embodiment of the present disclosure, the weight ratio of the polymerizable nematic liquid crystal monomer to the crosslinking agent is (0.8-3):1, preferably (1.2-2.5):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the acrylic monomer is (0.3-0.8):1, preferably (0.4-0.6):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the ionic liquid is (0.5-2):1, preferably (1.2-1.5):1. In the above embodiment, by selecting a composition with a preferred ratio, it is not only conducive to the formation of a liquid crystal-based polymer solid electrolyte with high mechanical stability and chemical stability, so that it is less affected by external factors such as water and oxygen, has high safety, and is not prone to flammable and explosive accidents; it is also conducive to improving the ionic conductivity of the liquid crystal-based polymer solid electrolyte, so that it exhibits excellent cycle stability and cycle life after being used in lithium metal batteries.

[0041] The second aspect of the present disclosure provides a method for preparing a liquid crystal based polymer solid electrolyte using the liquid crystal based polymer solid electrolyte composition according to the first aspect of the present disclosure, the method comprising:

[0042] (1) mixing the liquid crystal based polymer solid electrolyte composition with an organic solvent and stirring to obtain a polymer precursor solution;

[0043] (2) In-situ polymerization of the polymer precursor solution under ultraviolet light to obtain a liquid crystal based polymer solid electrolyte.

[0044] The liquid crystal-based polymer solid electrolyte provided by the present invention has lower raw material cost for preparation, looser requirements for the preparation environment, simpler preparation method, higher controllability of operation, and can produce a liquid crystal-based polymer solid electrolyte with high lithium ion transport performance and long-term stability, and has the potential for large-scale production and preparation, which is convenient for commercial application.

[0045] In one embodiment of the present disclosure, in step (1), the weight ratio of the liquid crystal-based polymer solid electrolyte composition to the organic solvent is (1-2.5):1, preferably (1.3-1.8):1; the organic solvent is selected from one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), anhydrous acetonitrile and acetone; in step (2), the conditions of the in-situ polymerization include: the wavelength of the ultraviolet light is 340-380nm, the light intensity is 20-40mW / cm 2 ; The temperature of in-situ polymerization is 25-35°C and the time is 20-35min.

[0046] A third aspect of the present disclosure provides a liquid crystal-based polymer solid electrolyte prepared by the method described in the second aspect of the present disclosure.

[0047] In one embodiment of the present disclosure, the liquid crystal-based polymer solid electrolyte is film-shaped, and the thickness of the film-shaped liquid crystal-based polymer solid electrolyte is 50 to 300 μm, preferably 120 to 200 μm. The influence of the thickness of the solid electrolyte in the application is as follows: For relatively thin solid electrolytes, the advantage is that the lithium ion transmission path is shorter, and lithium ions can move and migrate between the positive and negative electrodes more efficiently. However, if the solid electrolyte is too thin, it will increase the difficulty at the preparation process level, and the demolding process is prone to damage. At the same time, it is difficult to resist the generation of dendrites during the device cycle, causing short circuits; for thicker solid electrolytes, the advantage is that the difficulty of the preparation process can be greatly reduced, it is easy to demold, and it has a stronger ability to resist the growth of lithium dendrites, but it will make the lithium ion transmission path longer. Therefore, in actual operation, the optimal film thickness can be achieved by controlling the concentration of the polymer precursor solution and the thickness of the scraper.

[0048] The fourth aspect of the present disclosure provides a lithium metal battery, the lithium metal battery comprising a positive electrode material, a negative electrode material and an electrolyte, the electrolyte being the liquid crystal-based polymer solid electrolyte described in the third aspect of the present disclosure. Specifically, the positive electrode material of the lithium metal battery may be lithium iron phosphate, lithium iron manganese phosphate, NCM523, NCM811 or lithium cobalt oxide, the negative electrode material is lithium metal, and the lithium metal battery may be a button battery.

[0049] The raw materials used in the examples can all be obtained through commercial sources.

[0050] The SU8020 scanning electron microscope produced by Hitachi was used to analyze the microscopic morphology of the sample surface and cross section, and the working voltage of the analysis was 20 kV;

[0051] The ionic conductivity of the battery was tested using the Auto lab M204 electrochemical workstation produced by Swiss Metrohm.

[0052] Example 1

[0053] (1) 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (C6M, a polymerizable nematic liquid crystal monomer having a structural formula of Where n1-n2 are 3, R1-R4 are hydrogen, R5 is methyl, x, y, z are 1), ethylene glycol dimethacrylate (EGDMA, acrylate monomer, structural formula is Wherein m is 1), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM TFSI, imidazole ionic liquid, structural formula is ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, lithium salt, structural formula is ), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP, cross-linking agent, structural formula is ) and 1-hydroxycyclohexyl phenyl ketone (photoinitiator) were uniformly mixed in a weight ratio of 20%: 15%: 40%: 15%: 10%: 0.8% to obtain a liquid crystal based polymer solid electrolyte composition, the composition of which is shown in Table 1, and the structural formulas of the components are shown in Table 1. Figure 1 ;

[0054] The composition was dissolved in an equal mass of N-methylpyrrolidone solvent (NMP, an organic solvent), with a weight ratio of the composition to the organic solvent of 1.4:1, stirred for 30 minutes, and then placed in an ultrasonic dispersion device for 30 minutes to finally obtain a uniformly dispersed polymerization precursor solution;

[0055] (2) The polymerization precursor solution was injected into a sandwich mold consisting of two transparent glass sheets through a syringe. A PTFE spacer layer was used between the two glass sheets to control the gap thickness to 200 μm. In-situ polymerization was performed by irradiation with ultraviolet light of a wavelength of 365 nm and the light intensity was 20 mW / cm 2 The in-situ polymerization temperature is 25°C and the time is 20 min; then the glass sandwich mold is opened to obtain a polymer film;

[0056] (3) The polymer film was cut into discs with a diameter of 16 mm, placed in a vacuum oven, and vacuum dried at 80° C. for 24 h to obtain the final liquid crystal polymer solid electrolyte, denoted as LCPE.

[0057] Example 2

[0058] The same as Example 1, the only difference is that the proportions of the components in the liquid crystal based polymer solid electrolyte composition are different. The specific composition is shown in Table 1.

[0059] Example 3

[0060] The same as Example 1, the only difference is that the proportions of the components in the liquid crystal based polymer solid electrolyte composition are different. The specific composition is shown in Table 1.

[0061] Example 4

[0062] The same as Example 1, the only difference is that in step (1), the polymerizable nematic liquid crystal monomer used is 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-ethylbenzene, whose structural formula is Where n1~n2 are 3, R1~R4 are hydrogen, R5 is ethyl, x, y, z are 1; the acrylate monomer is diethylene glycol dimethacrylate, and its structural formula is m is 2; the ionic liquid is 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt, the lithium salt is bis(fluorosulfonyl)imide lithium salt, the crosslinking agent is trimethylolpropane tris(3-mercaptopropionate), the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the specific composition of each component in the formed composition is shown in Table 1; the organic solvent is N,N-dimethylformamide, and the weight ratio of the composition to the organic solvent is 1:1;

[0063] In step (2), the wavelength of the ultraviolet light is 365nm and the light intensity is 10mW / cm 2 The temperature of in-situ polymerization was 28°C and the time was 10 min.

[0064] Comparative Example 1

[0065] The same as Example 1, the only difference is that: in step (1), polyethylene glycol diacrylate (PEGDA, acrylate monomer) and 1-hydroxycyclohexyl phenyl ketone (photoinitiator, content of 0.8% by weight of PEGDA) are mixed to obtain a comparative composition, the specific composition of which is shown in Table 1; the comparative composition is dissolved in the same mass of N-methylpyrrolidone solvent (NMP) to finally obtain a comparative polymer solid electrolyte, recorded as P-PEGDA.

[0066] Comparative Example 2

[0067] The same as Example 1, the only difference is that: in step (1), 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene (C6M, a polymerizable nematic liquid crystal monomer) and 1-hydroxycyclohexyl phenyl ketone (photoinitiator, content is 0.8% by weight of C6M) are mixed to obtain a comparative composition, the specific composition of which is shown in Table 1; the comparative composition is dissolved in the same mass of N-methylpyrrolidone solvent (NMP) to finally obtain a comparative polymer solid electrolyte, recorded as P-PLC.

[0068] Comparative Example 3

[0069] The same as Example 1, the only difference is that in step (1), 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (C6M, a difunctional polymerizable nematic liquid crystal monomer) is replaced with the same amount of 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoate (a monofunctional polymerizable nematic liquid crystal monomer, the structural formula of which is: ), and finally obtained a comparative polymer solid electrolyte.

[0070] Comparative Example 4

[0071] The same as Example 1, the only difference is that in step (1), the acrylic acid ester monomer (the structural formula is: 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM TFSI, imidazole ionic liquid), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, lithium salt) and benzil dimethyl ether (photoinitiator) were uniformly mixed in a weight ratio of 56%:28%:15%:1% to obtain a comparative composition, the composition of which is shown in Table 1, and finally a comparative polymer solid electrolyte was obtained.

[0072] Table 1

[0073]

[0074]

[0075] Test Example 1

[0076] The polymer film obtained in Example 1 was removed and immersed in a methanol solution for 24 hours to remove organic impurities, and then vacuum dried in a vacuum oven at 60°C for 24 hours, and then the surface micromorphology of the polymer network was observed using a scanning electron microscope (SEM). In addition, the film was placed in liquid nitrogen for 2 minutes and then quickly fractured to obtain a complete cross-section, and the surface micromorphology of the polymer network was also observed using a scanning electron microscope (SEM). The results are as follows: Figure 1 shown.

[0077] It can be observed that the liquid crystal-based polymer solid electrolyte prepared by the present disclosure is in the form of a thin film with a thickness of only 200 μm, a shorter lithium ion transmission path, and lithium ions can move and migrate between the positive and negative electrodes more efficiently. The liquid crystal-based polymer solid electrolyte is mainly formed by polymerizable nematic liquid crystal monomers and acrylate monomers, and the formed polymer network presents a porous network structure, and the imidazole ionic liquid runs through it. The continuously oriented polymer network can not only provide sufficient physical support for the solid electrolyte film, but also the phase separation structure formed by the oriented porous network structure formed inside can form a continuous ion liquid channel, which provides a path for the rapid transportation of lithium ions and lays the foundation for the stable operation of the battery at room temperature.

[0078] Test Example 2

[0079] The solid electrolyte obtained in the embodiment and the comparative example is applied to lithium ion button cells as solid electrolyte. First, the battery is assembled in a glove box in the order of negative electrode shell-spring sheet-gasket-solid electrolyte-gasket-positive electrode shell, and then the button cell is packaged using a battery packaging machine. After packaging, the ionic conductivity is tested using the AC impedance method. The test results are shown in Table 2. The ionic conductivity of the solid electrolyte prepared in Example 1 changes with temperature as shown in Table 2. Figure 2 shown.

[0080] Test Example 3

[0081] A lithium sheet with a diameter of 12 mm was used as the negative electrode of the button cell, a lithium iron phosphate paste (LFP) was used as the positive electrode of the button cell, and the solid electrolyte prepared in the embodiment and the comparative example was used as the electrolyte to assemble a Li / LFP lithium metal battery. The electrochemical performance test was carried out on a LANHE, CA2001A battery test system, with a test voltage of 2.5 to 3.8 V, a temperature of 25±1°C, and a current density of 1C. The data of the first charge and discharge specific capacity, coulomb efficiency, 100 cycle capacity retention rate, and cycle number at 1C are shown in Table 2. The first charge and discharge curve and cycle performance curve of the Li / LCPE / LFP lithium metal battery assembled with the solid electrolyte of Example 1 are shown in Table 2. Figure 3 As shown. The capacity retention rate of 100 cycles at 1C = 100% * discharge capacity after 100 cycles / first cycle discharge capacity; the number of cycles refers to the number of cycles when the discharge capacity of the battery drops to 96.9% of the first cycle discharge capacity.

[0082] A lithium sheet with a diameter of 12 mm was used as the negative electrode of the button cell, NCM811 was used as the positive electrode of the button cell, and the solid electrolyte prepared in the embodiment and the comparative example was used as the electrolyte to assemble a Li / NCM811 lithium metal battery. The electrochemical performance test was carried out on a LANHE, CA2001A battery test system. The test voltage was 2.5-3.8 V, 25±1° C., and the current density was 0.2C. The first charge and discharge specific capacity, coulomb efficiency, 100 cycle capacity retention rate, and cycle number data at 0.2C are shown in Table 2. Among them, the 100 cycle capacity retention rate at 0.2C = 100% * discharge specific capacity after 100 cycles of the battery / first cycle discharge specific capacity, and the cycle number refers to the number of cycles when the discharge specific capacity of the battery drops to 92.9% of the first cycle discharge specific capacity.

[0083] Table 2

[0084]

[0085] The “-” indicates that the battery fails within 100 cycles.

[0086] As shown in Table 2, the liquid crystal polymer solid electrolytes of Examples 1 to 4 exhibited a thermal conductivity of 1.43 to 2.01 mS cm at 25°C. -1 The ionic conductivity of the comparative examples 1 to 4 at 25°C is only 0.56 to 1.21 mS cm -1 , indicating that the liquid crystal-based polymer solid electrolyte prepared by the composition disclosed in the present invention exhibits very superior ionic conductivity performance at room temperature.

[0087] The Li / LFP lithium metal battery assembled with the liquid crystal polymer solid electrolytes of Examples 1 to 4 exhibited excellent electrochemical properties at 25°C, wherein the solid electrolyte prepared in Example 1 cycled 1500 times at a current density of 1C, exhibiting a discharge specific capacity of 158.6mAh / g; the Li / NCM811 battery assembled with the liquid crystal polymer solid electrolytes of Examples 1 to 4 also exhibited stable electrochemical properties at 25°C, and the solid electrolyte prepared in Example 1 cycled 100 times at a current density of 0.2C, exhibiting a discharge specific capacity of 128.5mAh / g. It can be seen that the liquid crystal-based solid electrolyte exhibits excellent electrochemical properties. However, the first discharge specific capacity of the comparative polymer solid electrolytes of Comparative Examples 1 to 4 at a current density of 1C or 0.2C was relatively low, and the number of cycles was small, and the cycle life was short.

[0088] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0089] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0090] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A liquid crystal polymer solid electrolyte composition, characterized in that: The liquid crystal-based polymer solid electrolyte composition comprises a polymerizable nematic liquid crystal monomer, an acrylate monomer, an ionic liquid, a lithium salt, a crosslinking agent and an initiator; and the polymerizable nematic liquid crystal monomer comprises a bifunctional liquid crystal monomer.

2. The liquid crystal based polymer solid electrolyte composition according to claim 1, characterized in that: The polymerizable nematic liquid crystal monomer has a structure as shown in the following formula (1): In formula (1), n1 to n2 represent the number of -CH2-CH2- groups, and n1 to n2 are the same or different and are each independently selected from any integer between 1 and 9, preferably selected from any integer between 3 and 6; R1 to R5 are the same or different and are independently selected from hydrogen, a halogen group, a cyano group, an alkyl group having 1 to 5 carbon atoms, a halogenated alkyl group having 1 to 2 carbon atoms, and an alkoxy group having 1 to 2 carbon atoms; preferably, R1 to R5 are the same or different and are independently selected from one or more of hydrogen, a halogen group, a cyano group, a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group; x represents the number of R3, x is 0 or 1; y represents the number of R4, y is 0 or 1; z represents the number of R5, and z is 0 or 1.

3. The liquid crystal based polymer solid electrolyte composition according to claim 1, characterized in that: The polymerizable nematic liquid crystal monomer is selected from one or more of 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-methacryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-ethylacryloxyhexyloxy)benzoyloxy]-2-methylbenzene, 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-ethylbenzene, 1,4-bis[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene and 1,4-bis[4-(6-acryloxyhexyloxy)-3-methylbenzoyloxy]-2-methylbenzene.

4. The liquid crystal based polymer solid electrolyte composition according to claim 1, characterized in that: The acrylate monomer has a -CH2-CH2-O- structure, and the acrylate monomer includes one or more of a monofunctional acrylate monomer, a difunctional acrylate monomer, and a multifunctional acrylate monomer. Preferably, the acrylate monomer includes at least one difunctional acrylate monomer; the molecular weight of the difunctional acrylate monomer is 180 to 10,000; More preferably, the bifunctional acrylate monomer has a structure as shown in the following formula (2): In formula (2), m represents the number of -CH2-CH2-O-, and m is selected from any integer between 1 and 10, preferably selected from any integer between 1 and 5; Further preferably, the acrylate monomer is selected from one or more of ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate and pentaethylene glycol dimethacrylate.

5. The liquid crystal based polymer solid electrolyte composition according to claim 1, characterized in that: The cross-linking agent is selected from a thiol cross-linking agent, and the thiol cross-linking agent is selected from one or more of tetrakis(3-mercaptopropionic acid)pentaerythritol ester, (3-mercaptopropionic acid)ethylene glycol ester, trimethylolpropane tris(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionic acid)ester and 1,4-butanediol di(3-mercaptopropionate); The ionic liquid is selected from imidazolium ionic liquids and / or pyrrole ionic liquids, the cation of the imidazolium ionic liquid is selected from substituted or unsubstituted imidazolium cations, and the anion of the imidazolium ionic liquid is selected from one or more of halogen anions, halophosphate anions, haloalkane anions, halosulfonyl imide anions and halosulfonate anions; preferably, the imidazolium ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium hexafluorophosphate and 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide; The pyrrole ionic liquid is selected from 1-butyl-1-methylpyrrolidinobis(trifluoromethanesulfonyl)imide and / or 1-methyl-1-propylpyrrolidiniumbis(fluorosulfonyl)imide; The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate and lithium chloride; The initiator is selected from a photoinitiator, and the photoinitiator is selected from one or more of 1-hydroxycyclohexyl phenyl ketone, α-hydroxyisobutyrophenone and 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

6. The liquid crystal based polymer solid electrolyte composition according to claim 1, characterized in that: Relative to 100.8 parts by weight of the liquid crystal-based polymer solid electrolyte composition, the content of the polymerizable nematic liquid crystal monomer is 15 to 25% by weight, preferably 18 to 22% by weight; the content of the acrylate monomer is 30 to 50% by weight, preferably 35 to 45% by weight; the content of the ionic liquid is 10 to 20% by weight, preferably 13 to 17% by weight; the content of the lithium salt is 10 to 20% by weight, preferably 14 to 16% by weight; the content of the cross-linking agent is 5 to 15% by weight, preferably 8 to 12% by weight; the content of the initiator is 0.5 to 1.0% by weight, preferably 0.7 to 0.9% by weight.

7. The liquid crystal based polymer solid electrolyte composition according to claim 6, characterized in that: The weight ratio of the polymerizable nematic liquid crystal monomer to the cross-linking agent is (0.8-3):1, preferably (1.2-2.5):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the acrylic monomer is (0.3-0.8):1, preferably (0.4-0.6):1; the weight ratio of the polymerizable nematic liquid crystal monomer to the ionic liquid is (0.5-2):1, preferably (1.2-1.5):

1.

8. A method for preparing a liquid crystal based polymer solid electrolyte using the liquid crystal based polymer solid electrolyte composition according to any one of claims 1 to 7, characterized in that: The method comprises: (1) mixing the liquid crystal based polymer solid electrolyte composition with an organic solvent and stirring to obtain a polymer precursor solution; (2) In-situ polymerization of the polymer precursor solution under ultraviolet light to obtain a liquid crystal based polymer solid electrolyte.

9. The method according to claim 8, characterized in that In step (1), the weight ratio of the liquid crystal based polymer solid electrolyte composition to the organic solvent is (1-2.5):1, preferably (1.3-1.8):1; the organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, anhydrous acetonitrile and acetone; In step (2), the conditions for in-situ polymerization include: the wavelength of ultraviolet light is 340-380nm, the light intensity is 20-40mW / cm 2 ; The temperature of in-situ polymerization is 25-35°C and the time is 20-35min.

10. A liquid crystal polymer solid electrolyte prepared by the method according to any one of claims 8 to 9.

11. The liquid crystal based polymer solid electrolyte according to claim 10, characterized in that: The liquid crystal based polymer solid electrolyte is in the form of a film, and the thickness of the film-like liquid crystal based polymer solid electrolyte is 50 to 300 μm, preferably 120 to 200 μm.

12. A lithium metal battery, characterized in that: The lithium metal battery comprises a positive electrode material, a negative electrode material and an electrolyte, and the electrolyte is a liquid crystal-based polymer solid electrolyte as claimed in any one of claims 10 to 11.

Citation Information

Cited By

  • Fluorinated phase separation polymer ion gel electrolyte, preparation method and application thereof, and lithium metal battery

    CN120854670A

  • A fluorinated phase-separated polymer ion gel electrolyte, its preparation method and application, and lithium metal batteries.

    CN120854670B